Way Forward: Gastrointestinal Tract Endoscopy Work Flow Postlockdown Era - Sud, Randhir; Sud, Sukrit (Journal of Digestive Endoscopy, 2020)
Gastrointestinal tract endoscopy being an aerosol generating procedure increases the risk to staff and uninfected patients from a coronavirus disease 2019 patient. Social and physical distancing through “lockdown” has suppressed the spread of disease but will not eradicate it. Various endoscopy societies formulated guidelines to triage the patients and limit the work to only emergency and urgent cases and postpone “routine” endoscopies. Postlockdown infected vector pool will persist till an effective vaccine is widely available. Nonurgent cases cannot be postponed indefinitely. We need to identify infected symptomatic and asymptomatic individuals and create a safe environment for uninfected patients. Endoscopy staff protection through education, optimized manpower flow, and personal protective equipment usage and hand hygiene needs urgent attention. Proper environment sanitization, endoscope, and device reprocessing will remain important.
Keywords: severe acute respiratory syndrome coronavirus 2; health care workers; endoscopy; colonoscopy; aerosol